An AN ANALYSIS OF APOLOGY STRATEGIES IN THE ELLEN DEGENERES SHOW: PRAGMATICS APPROACH - Sabilla, Alfhiani; Jusmaya, Ance (LPPM Universitas Putera Batam, 2020)
This research discusses about apology strategies found in The Ellen DeGeneres Show. The aim of this research is to find out and describe the type of apology strategies based on Trosborg’s theory in Ellen DeGeneres talk show. The researcher used qualitative descriptive method. Data is collected based on utterances contained in Ellen DeGeneres show using non-participatory techniques. In gained the data, the researcher watches The Ellen DeGeneres show on YouTube, then read the subtitle and observe the subtitle to find out the data. Then, researcher used identity method in analyzing data. The finding is shown that there are three types from five types of apology strategies in this talk show. They are: 4 direct apology (expression of regret and offer of apology), 3 indirect apology (explicit explanation, lack of intent and explicit acknowledgment) and 3 remedial support (offer of repair, blaming someone else and concern for hearer).In conclusion, that direct and indirect apology the most frequent data found in the Ellen DeGeneres show. Keyword: pragmatics, speech act, apology strategies